Photothermal‐Activatable Liposome Carrying Tissue Plasminogen Activator for Photoacoustic Image‐Guided Ischemic Stroke Treatment. Issue 2 (17th November 2021) - Cai, Xiaolei; Bandla, Aishwarya; Wang, Can; Liu, Yu-Hang; Chuan, Chan Kim; Xu, Yu; Liu, Xingang; Xu, Shidang; Wu, Wenbo; Thakor, Nitish V.; Liu, Bin
Abstract : Ischemic stroke is a highly prevalent cause of mortality and morbidity. The only FDA‐approved treatment is thrombolysis using tissue plasminogen activator (tPA), which possesses a short effective time window. Real‐time recanalization monitoring is crucial to establish successful reperfusion and serves as a strong predictor of clinical outcomes. First‐line clinical imaging techniques, such as computed tomography and magnetic resonance imaging, are limited in their soft‐tissue resolution, scanning speed, and accessibility. Transcranial doppler ultrasound, the current gold standard for recanalization monitoring, is a blind technique and highly operator dependent. Herein, a photothermal‐activatable liposome carrying tPA for photoacoustic (PA) image‐guided therapy for real‐time and precise recanalization monitoring of ischemic stroke is designed. The liposome containing an organic molecule with propeller structures exhibits excellent photothermal properties and significantly amplified PA signals as compared with the widely used polymer nanoparticles. Near‐infrared (NIR) laser triggers rapid release of tPA for quick blood clot lysis in vitro. Administration of the liposome in a rat photothrombotic ischemia model facilitates high‐resolution PA imaging for precise real‐time recanalization assessment. Precisely controlled tPA release at the ischemic region is achieved by PA image‐guided NIR laser irradiation, which successfully dissolves the blood clot and restores perfusion, making this design promising for translational applications. Abstract : A photothermal‐activatable liposome carrying tissue plasminogen activator (tPA) is designed to provide photoacoustic image‐guided and photothermal‐controlled release of tPA for ischemic stroke treatment.